Correlation Between Spirituality and The Level of Psychological Well-Being in the Elderly at Banyuwangi Nursing Home - Aprilia, Niken; Kurdi, Fahruddin; Rasni, Hanny (Al-Hijrah Indonesia, 2024)
Background: Elderly in nursing homes face various problems such as a decline in body condition and health due to the aging process which has an impact on psychological well- being. Problems in psychological well-being can be addressed through spirituality, which functions as a coping mechanism. Purpose: This study aims to analyze the relationship between spirituality and the level of psychological well-being in elderly at nursing home in Banyuwangi. Methods: This study is a quantitative study, correlational study design with a cross sectional approach. The sample in this study consisted of 42 respondents selected using a total sampling according to inclusion and exclusion criteria. This study used the Daily Spiritual Experience Scale (DSES) questionnaire and the Psychological Well-Being Scale (PWBS) questionnaire. Results: Descriptive analysis showed that the majority of elderly at nursing home in Banyuwangi had a high level of spirituality (50.0%) and a high level of psychological well-being (38.1%). Based on the Kendall's Tau b correlation test, the p-value was 0.001, indicating there is relationship between spirituality and the level of psychological well-being in the elderly at nursing home in Banyuwangi. The results of the r-value was +0.487, show there is a positive correlation which means the higher the level of spirituality in the elderly, the higher the level of psychological well-being. Conclussion: spirituality has an important role in improving the psychological well-being of the elderly, so efforts can be made to improve the psychological well-being in the elderly by increasing spirituality in the elderly.